2004
DOI: 10.1002/jbm.b.30168
|View full text |Cite
|
Sign up to set email alerts
|

Micro/nanoscale mechanical and tribological characterization of SiC for orthopedic applications

Abstract: Micro/nanomechanical and tribological characterization of SiC has been carried out. For comparison, measurements on SiC, CoCrMo, Ti-6Al-4V, and stainless steel have also been made. Hardness and elastic modulus of these materials were measured by nanoindentation using a nanoindenter. The nanoindentation impressions were imaged using an atomic force microscope (AFM). Scratch, friction, and wear properties were measured using an accelerated microtribometer. Scratch and wear damages were studied using a scanning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 18 publications
1
48
0
Order By: Relevance
“…Although SiC has already seen some implementation in modern medical implants (Li et al, 2005), and previous studies have suggested that SiC is biocompatible with different cell lines (Coletti et al, 2007;Frewin et al, 2009b;Li et al, 2005), little research has been devoted to www.intechopen.com enhancing its biocompatibility via surface modification. In this work, we examined the possibility of increasing cellular proliferation and attachment on the (0001) Si face of 6H-SiC with PC12 and H4 using SAM with terminal methyl and amino groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although SiC has already seen some implementation in modern medical implants (Li et al, 2005), and previous studies have suggested that SiC is biocompatible with different cell lines (Coletti et al, 2007;Frewin et al, 2009b;Li et al, 2005), little research has been devoted to www.intechopen.com enhancing its biocompatibility via surface modification. In this work, we examined the possibility of increasing cellular proliferation and attachment on the (0001) Si face of 6H-SiC with PC12 and H4 using SAM with terminal methyl and amino groups.…”
Section: Resultsmentioning
confidence: 99%
“…First, we performed hydrogen etching in order to obtain well-ordered, atomically flat surfaces with reduced surface defect densities (Frewin et al, 2009a). The samples were cleaned as described in section 2.1. followed by a 5% diluted HF dip that results in OH termination of the surface (Li et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ChongTian et al adopt new techniques to prepare silicon carbide (SiC) foams, which possess high strength, appropriate elastic modulus and good machinable properties 9,10) . SiC foam has attracted much more research interest in the field of biomaterial in the past decade [11][12][13] . Previous experimental results already suggest that this new material has good biological safety 14) .…”
Section: Introductionmentioning
confidence: 99%
“…2) Among the conventional orthopedic alloys such as stainless steels, cobalt-base alloys, and titanium-base alloys that have been used in the medical device industry, [3][4][5][6][7][8] great attention has recently been paid to Ti/6Al/4V alloy, developed originally for use in aerospace applications, due to its comparatively lower modulus, high strength, superior corrosion resistance, and biocompatibility. [9][10][11][12][13][14][15][16] In particular, the excellent corrosion resistance and biocompatibility of Ti-6Al-4V is attributed primarily to the formation of a tenacious oxide layer upon contact with air.…”
Section: Introductionmentioning
confidence: 99%